Proyeksi Mutu Pendidikan Indonesia: Peluang dan Ancaman Artificial Intelligence (AI) Menuju Indonesia Emas 2045 - Fitrianingsih (PT. Nawa Edukasi Nusantara, 2025)
Artificial Intelligence (AI), currently regarded as one of the key innovations in technology, in fact carries both opportunities and threats for the quality of Indonesian education in the future. This study aims to critically examine the projected quality of Indonesian education in the era of Artificial Intelligence (AI) toward Golden Indonesia 2045. Accordingly, two research questions are proposed: (1) How is the quality of Indonesian education projected in the era of Artificial Intelligence in realizing Golden Indonesia 2045? (2) What forms of opportunities and threats does Artificial Intelligence pose to the quality of Indonesian education toward Golden Indonesia 2045? This study employs a narrative literature review method with a qualitative-descriptive approach. The findings indicate that the presence of AI opens opportunities in the form of personalized learning, improved accessibility of education, automated assessment, curriculum development, and administrative efficiency. On the other hand, AI also poses potential threats, including the digital divide, technological dependency, declining teacher-student interaction, widening inequality of opportunity, and risks to data privacy and security. Accordingly, this study recommends the need for education on the ethical use of AI and the improvement of teacher quality to keep pace with technological developments.